P856 Compositional changes in the gut microbiota of Korean inflammatory bowel disease patients are linked to clinical phenotypes. (25th January 2019) - Choi, C H; Kim, Y; Shin, S Y; Kim, K; Lee, K-M; Jung, S-A; Serrano, C; Lee, S C
Abstract: Background: Gut microbiota play a central role in pathogenesis of inflammatory bowel disease (IBD). We aimed to examine the differences of gut microbiota between Korean IBD patients and healthy controls (HC), and their relationship to disease phenotypes. Methods: We collected faecal samples from 70 ulcerative colitis (UC) and 12 Crohn's disease (CD) patients, and 81 HC. Faecal bacterial taxonomic composition was investigated using 16S sequencing. The obtained sequences were analysed using the BIOiPLUG pipeline (https://www.bioiplug.com ) to assess bacterial diversity and composition. The relationship between faecal bacteria and clinical pheotypes was analysed using Comparative Genomics (CG) pipeline of BIOiPLUG Apps. Clinical severity of UC was classified to remission, mild, moderate and severe by Mayo score. Disease extent of UC was classified to proctitis, left-sided colitis and extensive colitis. Results: The mean age and sex ratio were not different between the groups. Community α-diversity of faecal bacteria measured in Chao 1 was significantly lower in UC and CD, compared with HC ( p < 0.01). Β-diversity measured by Bray-Curtis dissimilarity in UC and CD was significantly different from that of HC ( p < 0.01). The β-diversity was also different between UC and CD ( p < 0.01). The greater extent of the UC was related to the lower α-diversity of the faecal bacteria. Also, the worse severity of the UC was related to the lower α-diversity. There were significant differences in abundance of some bacterial species between the groups . Eisenbergiella tayi, Parabacteroides goldsteinii, Akkermansia muciniphila, and Bacteroides intestinalis are 10 times or more abundant in HC than UC. Clostridium innocuum group, Lactobacillus paracasei group, Lactobacillus crispatus group, Bifidobacterium dentium group, Butyricicoccus pullicaecorum, Eggerthella sinensis, and Proteus vulgaris group are 10 times or more abundant in UC. Leuconostoc lactis group, Coprococcus eutactus group, Akkermansia muciniphila, Lactococcus garvieae group, Adlercreutzia equolifaciens group, Weissella confusa group, and Lactococcus lactis group are 100 times or more abundant in HC than CD. Proteus vulgaris group, Morganella morganii group, Turicimonas muris, and Dysgonomonas capnocytophagoides are 100 times or more abundant in CD. Conclusions: Gut bacterial dysbiosis in Korean IBD patients is characterised by alterations in biodiversity and composition. The degree of dysbiosis is associated with disease severity and extent in UC. There are some differences in bacterial abundancy between IBD patients than HC. These data may help discriminate disease phenotypes, predict clinical course, and discover new therapeutic targets in IBD.